Marketing mix strategy of intercity train service towards the enhancement of corporate image of KTM Berhad at Kuala Lumpur Central Station / Hana Azleen Amiruddin - Amiruddin, Hana Azleen (Faculty of Business and Management, 2007)
KTM Berhad operates several intercity train services under the brand name KTM Antarabandar (KTM Intercity). Most of the services operate from Kuala Lumpur Sentral Station in Kuala Lumpur. However, there are several train services which operate solely along the East Coast line between Tumpat and Gemas and then followed on to Singapore. Obviously ineffective promotion is one of the problem that KTMB face nowadays, eventhough their price of tickets are affordable and the service is quiet good, they should improve the way they promote their product and services in order to attract more customers to travel with train. The objective of this research is to figure out what are the factors of Marketing Mix that influence to the enhancement of the KTMB corporate image ill respect of intercity services. Furthermore, the survey which is respondent has been choose conveniently at KL Central will fulfilled the questionnaire that researcher will distribute later. Perhaps, this research will give KTMB some view from respondent that contribute to the improvement of KTMB intercity train services in the future. From the findings, this research has proved that promotional activities of KTMB Intercity services is the factor that need to improve more and product and services of KTMB Intercity itself has influence the passenger to use the service and also as a factor that enhance KTMB Intercity corporate image.